Organizational management improvement factors in the novice principal induction program - Muhammad Amin, Aney Marinda; Othman, Norasmah; Hamid, Aida Hanim A. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The need for effective principal in every school is critical and the demand for leadership talent is increasing especially among novice principals. Therefore, an effective induction program would be crucial to support novice principals in improving their knowledge and leadership skills. This quantitative study aims to determine the level of implementation of the novice principal induction program regarding professional development course, coaching, and mentoring; and to identify the main components that contribute to the improvement of organizational management among novice principals. A total of 417 novice principals who participated in the induction program in Malaysia provided their feedback in a questionnaire consisting of 44 items. The items include three components in the induction program, encompassing the professional development course, coaching, and mentoring in improving organizational management. The study found that the professional development course is the main component followed by coaching in improving the management skills of novice principals. Hence, novice principals’ learning in induction should be directly linked to their own professional development to increase the effectiveness of school operations and student achievement.